Formulation and Evaluation of Immediate Release Tablets of Linezolid - Sai Madhav Reddy, K (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT In this study Immediate Release Tablets of Linezolid were formulated by wet granulation method. Nine formulations (f2-f10) of immediate release oral tablets were prepared by using different disintegrants to get desired release profile as that of reference marketed product (f1). Evalution Parameters Like weight variation, hardness of the tablet,friability,thickness,disintegration test,drug content uniformity and in vitro release studies were performed. Formulation of linezolid having 8.0mg of HPC i.e., Formulation F-10 can be taken as an ideal or optimized formulation.